2000
DOI: 10.1038/sj.bmt.1702424
|View full text |Cite
|
Sign up to set email alerts
|

Granisetron (Kytril) plus dexamethasone for antiemetic control in bone marrow transplant patients receiving highly emetogenic chemotherapy with or without total body irradiation

Abstract: Keywords: antiemetic; bone marrow transplant; chemotherapy; dexamethasone; granisetron; total body irradiation Nausea, retching, and emesis are some of the most common unwanted effects associated with chemotherapy. These treatment side-effects represent a significant concern to the cancer patient.1 Nausea and vomiting are contributing factors to patient morbidity, and are critical factors in the patient's quality of life during treatment. Additionally, emetic episodes often influence the continuation of treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 10 publications
3
23
0
Order By: Relevance
“…These studies have substantiated the efficacy of granisetron and ondansetron for prevention of N/V associated with high-dose conditioning regimens, however, different dosing strategies and end points have made comparisons of these results difficult. One such study was conducted by Abbott et al 18 and evaluated the efficacy of intravenous granisetron plus intravenous dexamethasone 10 mg administered daily until 24 h after conditioning therapy was complete. Only 1% of 100 patients enrolled failed to respond, however, the response criteria were different than those used in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have substantiated the efficacy of granisetron and ondansetron for prevention of N/V associated with high-dose conditioning regimens, however, different dosing strategies and end points have made comparisons of these results difficult. One such study was conducted by Abbott et al 18 and evaluated the efficacy of intravenous granisetron plus intravenous dexamethasone 10 mg administered daily until 24 h after conditioning therapy was complete. Only 1% of 100 patients enrolled failed to respond, however, the response criteria were different than those used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Outside of the HSCT setting, numerous studies have concluded that these agents provide equivalent control of N/V induced by highly emetogenic chemotherapy when administered at equipotent doses. [2][3][4][5][6][7][8] Although three of these agents have been extensively studied in HSCT patients over the last 8 years, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] limited data directly comparing these agents is available. [21][22][23] Ondansetron, the first 5-HT 3 receptor antagonist approved in the United States, has been the most widely studied and is most effectively used in combination with corticosteroids for prevention of CINV; granisetron's effects are also enhanced with the use of corticosteroids.…”
mentioning
confidence: 99%
“…19 For patients receiving high-dose chemotherapy or chemo/ radiotherapy regimens in association with hematopoietic stem cell support, a number of studies suggest that antiemetic control may be a greater challenge in this setting. 17,[20][21][22][23][24][25] In the current prospective trial, we have clearly demonstrated that despite the use of standard prophylactic treatments, antiemetic control is indeed suboptimal for patients receiving allogeneic or autologous hematopoietic stem cell transplants and appears to be inferior to the results obtained with standard-dose chemotherapy. Limitations of the study include the diverse conditioning regimens, antiemetic treatments, and small sample size.…”
Section: Discussionmentioning
confidence: 91%
“…14 Other prospective studies did not analyze these predictive factors. 22,23 Of note, none were found to have a significant impact. There was a trend toward less emesis in patients receiving dexamethasone and perhaps this would have achieved significance with a larger patient sample.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] However, a number of recipients still suffer from uncontrollable CINV. [5][6][7][8][9][10] Therefore, additional options to reduce CINV in these patients are needed.…”
mentioning
confidence: 99%